Children's scale errors: A by‐product of lexical development?. Issue 2 (27th September 2018) - Grzyb, Beata J.; Cangelosi, Angelo; Cattani, Allegra; Floccia, Caroline
Abstract: Scale errors occur when young children seriously attempt to perform an action on an object which is impossible due to its size. Children vary substantially in the incidence of scale errors with many factors potentially contributing to these differences, such as age and the type of scale errors. In particular, the evidence for an inverted U‐shaped curve of scale errors involving the child's body (i.e., body scale errors), which would point to a developmental stage, is mixed. Here we re‐examine how body scale errors vary with age and explore the possibility that these errors would be related to the size and properties of children's lexicon. A large sample of children aged 18–30 months ( N  = 125) was tested in a scale error elicitation situation. Additionally, parental questionnaires were collected to assess children's receptive and expressive lexicon. Our key findings are that scale errors linearly decrease with age in childhood, and are more likely to be found in early talkers rather than in less advanced ones. This suggests that scale errors do not correspond to a developmental stage, and that one determinant of these errors is the speed of development of the linguistic and conceptual system, as a potential explanation for the individual variability in prevalence. Abstract : Scale errors linearly decrease with age in childhood, and are more likely to be found in early talkers rather than in less advanced ones. This suggests that one determinant of these errors is the speed of development of the linguistic and conceptual system.